2018
DOI: 10.1155/2018/6714282
|View full text |Cite
|
Sign up to set email alerts
|

Total Flavonoids from Radix Glycyrrhiza Exert Anti‐Inflammatory and Antitumorigenic Effects by Inactivating iNOS Signaling Pathways

Abstract: Inducible nitric oxide synthase (iNOS) plays an important role in inflammation, which has also been considered as a major driver of breast cancer disease progression. Radix Glycyrrhiza (RG) has been broadly used for its anti-inflammatory and antitumorigenic effects. However, the mechanisms of regulation of iNOS in inflammation and cancer have not been fully explored. Total flavonoids isolated from RG (TFRG) exhibited anti-inflammatory activity through the regulation of ERK/NF-κB/miR-155 signaling and suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 40 publications
0
24
0
1
Order By: Relevance
“…It was reported that polyphenols can suppress NF-kB activation and translocation into the nucleus of the activated B cells ( Annunziata et al., 2020 ). Plant extracts with anti-inflammatory effects mediated by iNOS inhibition and nitro-oxidative stress reduction may be an adjuvant alternative therapeutic option for tumor cells proliferation and metastasis inhibition ( Jiang et al., 2018 ). Turpentine administration significantly increased NOx (p < 0.001), and pretreatment with GP extracts caused a concentration-dependent reduction of NOx, the fresh GP extracts having a stronger inhibitory effect than the fermented GP extracts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that polyphenols can suppress NF-kB activation and translocation into the nucleus of the activated B cells ( Annunziata et al., 2020 ). Plant extracts with anti-inflammatory effects mediated by iNOS inhibition and nitro-oxidative stress reduction may be an adjuvant alternative therapeutic option for tumor cells proliferation and metastasis inhibition ( Jiang et al., 2018 ). Turpentine administration significantly increased NOx (p < 0.001), and pretreatment with GP extracts caused a concentration-dependent reduction of NOx, the fresh GP extracts having a stronger inhibitory effect than the fermented GP extracts.…”
Section: Resultsmentioning
confidence: 99%
“…The toxicity hypothesis indicates that high levels of NO induce mitochondrial respiratory inhibition, ATP depletion, DNA deamination, oxidation, and nitration. The hypothesis of the cytoprotective role of NO states that NO protects cells against lipid peroxidation by reaction with sulfhydryl groups in proteins (Jiang et al, 2018). Because flavonols inhibit NO production (Semwal et al, 2016) and NO accumulation (Dai et al, 2013), the reduction of NO may be correlated with the polyphenol content.…”
Section: In Vivo Antioxidant Effectsmentioning
confidence: 99%
“…Extracts were dissolved with DMSO before use. TFRG was obtained as described previously [10], and no endotoxin existed in it by endotoxin test.…”
Section: Methodsmentioning
confidence: 99%
“…В исследовании Y.X. Jiang [33] доказано, что растительные экстракты Radix Glycyrrhiza, обладающие противовоспалительной активностью, нацелены на iNOS, соответственно, снижают окислительный/нитрозативный стресс и являются полезными химиопревентивными агентами против развития рака молочной железы и/или метастазов. В исследовании моделировали мышам рак молочной железы путем инъекции онкоклеток MDA-MB-231, которые взяли из биоптата опухоли ткани молочной железы у пациенток с диагнозом «рак молочной железы эстрогензависимый».…”
Section: симптомunclassified